Metastases to the Kidney: An Analysis of 35 Cases and a Review of Literature - Chen, Jinchao; Qi, Nienie; Zhu, Shaoxing (Frontiers in Oncology, 2021)
Introduction In addition to being rare, metastases to the kidney raise issues with clinicians regarding their treatment. Materials and Methods We retrospectively studied 35 cases of diagnosed renal metastases. The clinical characteristics, imaging features, pathological features, diagnosis, and treatment were analyzed and Kaplan-Meier methods and Cox regression analysis were used to calculate overall survival (OS) and influencing factors. Results: The average age of patients was 62 years old and 40% presented with symptoms. The most common primary tumor was lung cancer (60%) and 2 patients had renal metastases coexisting with renal cell carcinoma. The average interval from primary tumor to renal metastasis was 29.4 months. Only 45.5% of the patients receiving enhanced CT were diagnosed with renal metastases. Renal biopsy was performed in 16 patients (45.7%) and 15 cases (93.8%) were diagnosed. Twenty-one patients (60%) received surgical treatment. On the whole, the median OS was 44 months for patients who underwent renal surgery, and 52 months for patients who did not (P=0. 672). But for patients without other site metastasis, surgery could significantly prolong the OS (P=0.001). Conclusion Although rare, renal tumors with primary tumors of other organs need to consider the possibility of renal metastasis, which can be diagnosed by imaging examination and puncture biopsy. For patients without other metastases, surgical intervention of renal lesions can be considered.